Case study on Esophageal Squamous Cell Carcinoma (ESCC). - Fatemeh Keikha (20917848) (2025)
(A) State specific DNB subnetwork identified from GSE199654 across six ESCC states, including 28 genes (14 known, 14 novel). (B) State wise AUROC for multiclass classification using DNBs.